Organic chemistry - Brown, William Henry, 1932-, editor 379405 (Belmont, CA : Brooks/Cole, Cengage Learning)
Renowned for its unified mechanistic themes, emphasis on biological examples, use of applied problems from the pharmaceutical field, and unrivaled full-color visuals, ORGANIC CHEMISTRY, Sixth Edition, delivers cutting-edge coverage packed with reader-friendly features. Offering a clear presentation, the book offsets reaction mechanisms in a stepwise fashion and emphasizes similarities between related mechanisms, using just four different characteristics: breaking a bond, making a new bond, adding a proton and taking a proton away. Numerous resources assist in mastery of key concepts and problem-solving skills, including a running margin glossary, a mini in-text study guide, medicinal chemistry problems, unique roadmap problems, and more in-chapter examples than any other book.